Study on the impact of learning engagement on the subjective wellbeing of empty nesters in rural China - Zeng, Ruirang; Shi, Huiqin; Wu, Huiqi; Sun, Lixin (Frontiers in Psychology, 2024)
With the rapid development of China's socio-economic landscape and shifts in population structure, rural empty nesters have increasingly become a focal point of social concern. Compared to their urban counterparts, rural empty nesters face more life challenges and psychological stress, making their subjective well-being a significant issue. This study explores the impact of learning engagement on the subjective well-being of rural empty nesters in China, aiming to provide theoretical support and policy recommendations to enhance their well-being. Using a random sampling method, the study focused on elderly learners aged 50 and above from counties within Z Province, N City, where elderly learning is relatively concentrated. Data were processed using SPSS 27.0 software. The findings indicate that there is a significant difference in subjective well-being between rural empty nesters and rural non-empty nesters, with rural empty nesters exhibiting lower subjective well-being and more passive involvement in learning activities. Learning engagement has a significant effect on improving the subjective well-being of rural empty nesters, with a notable positive correlation between learning engagement dimensions and subjective well-being. Compared to rural non-empty nesters, learning engagement has a more pronounced positive effect on the subjective well-being of rural empty nesters.